Radioactivity of some natural and artificial radionuclides in coastal seawater at Ninh Thuan, Ba Ria - Vung Tau and Ca Mau provinces in 2018 - Nguyen Dinh, Tung; Le Nhu, Sieu; Nguyen Van, Phuc; Nguyen Van, Phu; Tran Dinh, Khoa; Vuong Thi Thu, Hang; Nguyen Thi Thanh, Nga; Le Thi Minh, Tuyen (Nuclear Science and Technology, 2020)
Radioactivities of some natural (Ra-226, Th-232, U-238, Po-210) and artificial (Cs-137, Sr-90 and Pu-239,240) radionuclides in coastal seawater at monitoring points of Ninh Thuan, Ba Ria - Vung Tau and Ca Mau provinces were analyzed quarterly in the year of 2018. Radioactivities of Ra-226, Th-232, U-238, and Cs-137 had been determined by simultaneous precipitation method and measured on low-level background gamma spectrometer; the radioactivities of Po-210 and Pu- 239,240 had been analyzed by radiochemical separation method and measured on alpha spectrometer; the radioactivity of Sr-90 had been analyzed by radiochemical separation method and measured on low-level background beta counting system. The ranges of radioactivities of Ra-226, Th-232, U-238, Po-210, Cs-137, Sr-90, and Pu-239,240 were 2.71 ÷ 15.91, 3.45 ÷ 35.93, 3.02 ÷ 21.47, 1.51÷ 6.74, 0.88 ÷ 1.68, 1.08 ÷ 1.86 and 0.0026 ÷ 0.0062 mBq/L, with the average values of 6.37, 12.67, 8.34, 3.29, 1.36, 1.46 and 0.0043 mBq/L, respectively. The results shown that the radioactivities of the above-mentioned radionuclides varied between the seawaters at Ninh Thuan, Ba Ria - Vung Tau and Ca Mau seawater. Additionally, physicochemical parameters in seawater were also surveyed to assess their impact on the fluctuations of the above radionuclides.